(untitled) (International Seven Journal of Multidisciplinary, 2021)
This article presents a comprehensive case study of the strategic and technical contributions of Brazilian mechatronics engineer Celio Francisco Filho, who led a critical international tryout in France for the implementation of CNC (Computer Numerical Control) automation at Dyna, a long-established manufacturer of windshield wiper systems. The project involved validating the performance and operational feasibility of a custom-developed CNC machine intended to automate the production of wiper arm rods—components that require high dimensional precision and structural integrity. Filho was responsible for overseeing the machine’s calibration, sensor integration, tolerance testing, and communication with control systems. His leadership ensured not only the technical success of the tryout but also facilitated cultural and operational alignment between international partners. Upon successful validation, the CNC system was transferred to Dyna’s Brazilian production line, resulting in substantial improvements in productivity, quality control, and data integration. This case underscores the importance of combining engineering expertise with global collaboration, illustrating how individual leadership can drive industrial innovation and support digital transformation in emerging markets. The study also contributes to broader discussions on smart manufacturing, retrofit automation, and the evolving role of engineers in globalized production ecosystems.